Assessing Risks of Patient- and Family-Initiated Assaults and Developing Training Programs for Prevention and Response in Healthcare Settings (The Review of Diabetic Studies, 2025)
Background: Violence and assaults directed at healthcare workers by patients or their families represent a growing global concern, with significant implications for staff safety, psychological well-being, quality of care, and healthcare system sustainability. Such incidents are particularly prevalent in high-stress clinical environments, including emergency departments, psychiatric units, and primary care settings. Systematic assessment of assault risk and the development of structured training programs are increasingly recognized as essential strategies for prevention and effective response. Objective: This systematic review aims to synthesize existing evidence on (1) methods used to assess the risk of assaults by patients or their families toward healthcare workers, and (2) the effectiveness of training programs designed to prevent, de-escalate, and respond to such incidents. Methods: A systematic literature search was conducted across major electronic databases, including PubMed, Scopus, Web of Science, and CINAHL, following PRISMA guidelines. Studies published in English that addressed risk assessment tools, predictive factors, or training and educational interventions related to patient- or family-initiated assaults in healthcare settings were included. Data were extracted on study design, setting, target population, risk assessment approaches, training components, and reported outcomes. Study quality was appraised using standardized critical appraisal tools. Results: The reviewed studies identified multiple risk factors for assaults, including patient-related factors (e.g., psychiatric illness, substance use, pain, and cognitive impairment), environmental factors (e.g., overcrowding, long waiting times, inadequate security), and organizational factors (e.g., staffing shortages and lack of clear policies). Risk assessment approaches ranged from structured screening tools and incident reporting systems to observational and environmental risk audits. Training programs commonly focused on communication skills, early recognition of warning signs, de-escalation techniques, personal safety strategies, and post-incident reporting and support. Overall, evidence suggests that multifaceted training programs, particularly when combined with organizational and environmental interventions, are associated with improved staff confidence, reduced incidence of assaults, and better reporting practices. Conclusion: Assessing the risk of assaults from patients or their families and implementing comprehensive training programs are critical components of workplace violence prevention in healthcare settings. Effective strategies require an integrated approach that combines individual training, systematic risk assessment, supportive organizational policies, and a culture of safety. Further high-quality, longitudinal studies are needed to determine the long-term impact of these interventions on assault rates and staff well-being.